2015
DOI: 10.1111/jpn.12288
|View full text |Cite
|
Sign up to set email alerts
|

Micronized fibres affect in vitro fermentation under normal buffered and osmotic stress conditions using porcine inocula

Abstract: In this in vitro study, the modified Hohenheim gas test was used to determine fermentation activity and bacterial composition of pig's faecal microbial inoculum, when fermenting a standard pig diet with varying levels of crude protein (CP; 20, 24 and 28% CP), and supplemented with one of three fibre sources manufactured by micronization treatment. These were wheat envelopes (MWE), pea fibre (MPF) and lupine fibre (MLF). For comparison, inulin was used. As intestinal bacteria have to cope with varying osmotic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
(59 reference statements)
2
4
0
Order By: Relevance
“…did not increase following addition of inulin or cellobiose. For inulin and Lactobacillus spp., this is in agreement with earlier HGT studies (Aumiller et al., ; Rink, Bauer, Eklund, Mosenthin, et al., ). In addition, an in vitro study of Blaise et al.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…did not increase following addition of inulin or cellobiose. For inulin and Lactobacillus spp., this is in agreement with earlier HGT studies (Aumiller et al., ; Rink, Bauer, Eklund, Mosenthin, et al., ). In addition, an in vitro study of Blaise et al.…”
Section: Discussionsupporting
confidence: 94%
“…did not increase following addition of inulin or cellobiose. For inulin and Lactobacillus spp., this is in agreement with earlier HGT studies(Aumiller et al, 2015;. In addition, an in vitro study of Blaise et al(2011) using faeces of sows as microbial inoculum did not reveal any positive effect of cellobiose on Bifidobacterium spp.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Aumiller et al. (2015) and Chau et al. (2007) found micronization of wheat bran to solubilize part of its dietary fiber and to make it better fermentable by porcine inocula.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the protein was probably closely associated with the insoluble pericarp cell walls. Aumiller et al (2015) found that micronizing wheat bran makes its protein available and in vitro fermentable by pig fecal microbiota. Indeed, significantly more ammonia and BSCFA are produced than when coarse wheat bran is fermented.…”
Section: Protein Fermentationmentioning
confidence: 99%